Pendidikan Anak Usia Dini menurut Islam - Iyoh Mastiyah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2007)
Child is a gift from god and trusteeship all at once. parents are imperatively obliged to take care and educate their children appropriately with Allah’s command, in order that child can grow and develop optimally, to be educated people and good personality. but, in a reality it is shown that there have been many of children experienced moral decadence, even the dare to do violence and criminal. this condition might be caused by education accepted by the children in the early period was not parallel with the Islamic education principle. this paper will explain the child education according to Islam.